2017
DOI: 10.1097/nmd.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Comfortably Numb

Abstract: Evidence suggests that both dissociation and negative affect (NA) may precipitate binge eating. The extent to which dissociation may impact the experience of negative affect around binge eating is unclear. Women with bulimia nervosa completed a two-week ecological momentary assessment protocol of dissociation, NA, and binge eating. Multilevel modeling was used to examine dissociation as a moderator of NA preceding and following binge eating. NA was greater at the time of binge eating for participants higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While some studies have found that NA temporarily decreases during LOC ( 100 , 101 ), an equal number have found that NA remains constant or increases across LOC ( 102 , 103 ). One study suggests that people with greater overall dissociative tendencies experience more rapid decreases in NA after LOC ( 87 ). However, Mason et al ( 87 ) did not examine emotions or dissociation during LOC itself, and it therefore remains unclear whether a dissociative experience during LOC may temporarily reduce NA, as predicted by escape theory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some studies have found that NA temporarily decreases during LOC ( 100 , 101 ), an equal number have found that NA remains constant or increases across LOC ( 102 , 103 ). One study suggests that people with greater overall dissociative tendencies experience more rapid decreases in NA after LOC ( 87 ). However, Mason et al ( 87 ) did not examine emotions or dissociation during LOC itself, and it therefore remains unclear whether a dissociative experience during LOC may temporarily reduce NA, as predicted by escape theory.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests that people with greater overall dissociative tendencies experience more rapid decreases in NA after LOC ( 87 ). However, Mason et al ( 87 ) did not examine emotions or dissociation during LOC itself, and it therefore remains unclear whether a dissociative experience during LOC may temporarily reduce NA, as predicted by escape theory. Rather than replacing more aversive negative emotions with less unpleasant ones, LOC seems most likely to decrease low arousal negative emotions (e.g., boredom) and increase high arousal emotions that may be more distressing (e.g., guilt, anger at self) ( 101 , 104 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite many studies focusing on the relationship between trauma and dissociation in EDs (McShane & Zirkel, 2008;Oliosi & Dalle Grave, 2003;Vanderlinden, Spinhoven, Vandereycken, & van Dyck, 1995;, especially in relation to the bulimic symptoms (Cowan & Heselmeyer, 2011;La Mela, Maglietta, Castellini, Amoroso, & Lucarelli, 2010;Mason et al, 2017;Palmisano et al, 2018;Rodriguez-Srednicki, 2002), a thorough evaluation of the scientific literature showed that few data exist about this relationship in BED. Indeed, only two studies (Dalle Grave, Oliosi, Todisco, & Vanderlinden, 1997;Dalle Grave, Rigamonti, Todisco, & Oliosi, 1996) highlighted that BED subjects had higher scores of traumatic experiences and dissociation compared with OB non-BED subjects and healthy controls.…”
Section: Introductionmentioning
confidence: 99%